The perceptions of Australian physical preparation coaches about how to enhance ball release speed in elite male and female cricket pace bowlers - Letter, R. T.; Dwyer, D. B.; Drinkwater, E. J.; Feros, S. A. (The Journal of Strength and Conditioning Research, 2025)
This study describes the perceptions of Australian physical preparation coaches regarding the development of ball release speed in elite male and female cricket pace bowlers. Seven physical preparation coaches, who had at least 3 years' experience and were responsible for the physical development of adult Australian state-, territory-, or national-level male or female pace bowlers volunteered to participate in this study. Coaches engaged in a 30-60-minute semistructured, open-ended interview, where they answered questions regarding their current physical development practices and beliefs, and sex-related considerations in the development of ball release speed from a physical development perspective. A 6-step reflexive thematic analysis was conducted, which revealed 3 central themes (and subthemes): (a) strength qualities (improvement of maximal strength, development of general strength and movement competency that underpins more advanced strength qualities, and improvement of rate of force development and power), (b) conditioning qualities (development and maintenance of aerobic capacity, and improvement of high-speed running qualities), and (c) sex differences (physical qualities and exposure to professional training environments). Most physical preparation coaches believed the following physical qualities should be targeted in both sexes: (a) lower body maximal strength, (b) lower body reactive strength, (c) upper body pulling strength, (d) upper body overhead pulling power, (e) aerobic capacity (an adequate base), and (f) maximal sprint speed. Further observational and experimental studies are required to objectively understand how some of these physical qualities influence ball release speed in each sex.